Shallow Groundwater Level Monitoring in the Kathmandu Valley: Investigating Citizen Scientist Performance and Groundwater Level Data Fluctuation - Mandal, Rohinee Bishwas; Acharya, Sangharsh; Adhikari, Sadhana; Rijal, Kaushal; Duwal, Sudeep; Neupane, Sanjiv (International Journal on Engineering Technology, 2025)
Shallow groundwater level monitoring is crucial for the sustainable management of water, particularly in rapidly growing cities like the Kathmandu Valley (Valley). Engaging local communities as citizen scientists (CS) offers cost-effective data collection and creates awareness about groundwater status and management practices. This study investigates the performance of citizen scientists (regularity and data submission error) in groundwater level monitoring and evaluating the groundwater fluctuation trend in the Valley. During 2020, 68% of the groundwater CS was categorized as regular. In 2021 and 2022, regularity increased to 91% compared to the previous years, and regularity decreased in 2023 and increased in 2024. Meanwhile, a rise in the percentage of CS sending incorrect data was observed. Despite these fluctuations, the overall error percentage was very low (<8%), highlighting the reliability of the CS-collected data. The monthly groundwater level was recorded from 2020 to 2024 by citizen scientists mobilized across the Valley. Groundwater levels were shallower during the monsoon and post-monsoon months, while in pre-monsoon and winter, the levels were observed to be deeper. The study demonstrates the reliability of CS-collected data and highlights the seasonal trends in the shallow groundwater wells in the Valley, while also demonstrating the power of citizen science in improving the monitoring and sustainable management of groundwater.